(untitled) (American Journal of Islam and Society, 2013)
During April 2012, Salafi Muslims in Germany launched a Qur’an giveaway program to save non-Muslims from hell. Soon after, public debates emerged in the national media concerning broader Muslim transgressions in Europe. Especially the Turks, 3 million strong and two-thirds of Germany’s Muslims according to the Federal Migration and Refugees Office, underwent further scrutiny. The August 17, 2012, issue of the popular news magazine Der Spiegel posited why Turkish Muslims escaped the backlash against Islamist radicalism this time: Despite their proud Muslim identity, Turks living in Europe yearn to be integrated and feel at home in Germany. Until recently, migration scholars emphasized the incompatibility between Islam and western values, thereby portraying European Turks as another Muslim community that defied assimilation. Localizing Islam challenges this scholarship and explains why Turks feel at home in Europe. It compares several Turkish Sunni organizations in Germany and the Netherlands, reinvents ways they interpret Islam, and argues that Islam’s inner diversity has endured within the European context ...